Physical activity and lung cancer screening (PALS): feasibility randomised controlled trial of exercise and physical activity in lung cancer screening - Asha Bonney; Catherine L. Granger; Daniel Steinfort; Cameron Patrick; Henry M. Marshall; Kwun M. Fong; Renee Manser (Respiratory Research)
Abstract Background There is increasing evidence that screening provides a catalyst for behavioural change. Low physical activity (PA) levels are a potentially modifiable risk factor for developing lung cancer. This study aims to assess the feasibility and safety of a semi-supervised 8-week multi-modal exercise program to improve health-related quality of life and PA levels of participants of lung cancer screening. Methods Participants without lung cancer from a single Australian International Lung Screen Trial (ILST; NCT02871856) site were invited to this feasibility randomised controlled trial. Enrolled participants were randomised to usual care, written material, or a home-based exercise program (in addition to written material). Assessments occurred at baseline, 9 weeks, and 6 months. Results 75 participants were enrolled over a 3-month period in 2022 (consent rate of 67%). 43% of participants were female, median age 66 years old (IQR 62, 73). Of the 25 participants randomised to the home-based exercise program, 22 participants (88%) attended > 70% of weekly sessions. 99% (74/75) of study participants attended their 9-week and 6-month follow-up assessments. Conclusions This study confirms the feasibility and high compliance of delivering a semi-supervised 8-week multi-modal exercise program to participants of a lung cancer screening program. It was safe, with no adverse events. Clinical trial registration Australian Clinical Trials Register https://www.australianclinicaltrials.gov.au ACTRN12622001001785.